Pengaruh Pijat Endorphin Terhadap Kecemasan dalam Menghadapi Persalinan Pada Ibu Hamil Primigravida Trimester III - sartika, sartika; Noorlinda, Noorlinda (JURNAL KESEHATAN TERAPAN, 2025)
High levels of anxiety during pregnancy, especially approaching childbirth, can negatively impact both maternal and fetal health. One non-pharmacological intervention that has shown potential in reducing anxiety is endorphin massage—a light-touch therapy that stimulates the release of endorphins, which act as natural pain relievers and promote a sense of comfort. This study aimed to analyze the effect of endorphin massage on anxiety levels among third-trimester primigravida mothers facing labor. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed. The study involved 20 third-trimester primigravida participants. The intervention consisted of four sessions of endorphin massage, and anxiety levels were assessed using a modified version of the Hamilton Rating Scale for Anxiety (HRS-A). The results indicated a significant decrease in anxiety, with the mean score dropping from 3.5 before the intervention to 1.55 after. The Wilcoxon test showed a p-value of 0.000 (< 0.05), confirming a statistically significant effect of endorphin massage on reducing anxiety. These findings suggest that endorphin massage is an effective non-pharmacological method to lower anxiety levels and enhance maternal psychological preparedness and comfort prior to childbirth.